Grain size and grain boundary effects on the mechanical behavior of fully stabilized zirconia investigated by nanoindentation - Lian, Jie; Garay, Javier E.; Wang, Junlan (Scripta materialia, 2007)
Mechanical behavior of fully yttria stabilized zirconia (F-YSZ) was investigated by nanoindentation. The coarse- and fine-grained materials displayed similar reduced modulus and hardness. Clear pop-in was observed in coarse-grained F-YSZ, with the pop-in loads varying with grain orientation and distance from the grain boundary. Pop-in was not clear in nanocrystalline F-YSZ. The lower hardness of the grain boundary and the similar hardness of the two grain-sized materials indicate an intrinsic atomic structure difference in the coarse- and fine-grained F-YSZ.